The need for patient-focused therapy for children and teenagers with allergic rhinitis - Santos, Alexandra F (2017)
Allergic rhinitis is a common problem in childhood and adolescence, with a negative impact on the quality of life of patients and their families. The treatment modalities for allergic rhinitis include allergen avoidance, anti-inflammatory symptomatic treatment and allergen specific immunotherapy. In this review, four cases of children with allergic rhinitis are presented to illustrate how the recently published EAACI Guidelines on Pediatric Allergic Rhinitis can be implemented in clinical practice.